2017
DOI: 10.1016/j.materresbull.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion- and cathodo-luminescence properties of Yb3+/Ho3+/Li+ tridoped Lu6O5F8 nanoparticles

Abstract: Yb 3+ /Ho 3+ /Li + tridoped Lu 6 O 5 F 8 as a novel phosphor was prepared by a coprecipitation method. It is found that Li + doping could enhance the emission intensity of Yb 3+ /Ho 3+ codoped Lu 6 O 5 F 8 both under the excitation at 980 nm and low-voltage electron beam. Under 980 nm laser excitation, the intensity of red emission is slightly stronger than that of green emission, generating an overall yellow output in Lu 6 O 5 F 8 :20%Yb 3+ ,1%Ho 3+ ,x%Li + (0≤x≤8) nanoparticles, and the reason for this pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Guo et al . revealed that the Li + doping could enhance the emission intensity of Yb 3+ /Ho 3+ codoped Lu 6 O 5 F 8 nanoparticles 21 . Many researches show that the codoping of non-luminous ions into RE 3+ ions doped upconverting materials is a promising way to increase the intensity of upconversion emission.…”
Section: Introductionmentioning
confidence: 98%
“…Guo et al . revealed that the Li + doping could enhance the emission intensity of Yb 3+ /Ho 3+ codoped Lu 6 O 5 F 8 nanoparticles 21 . Many researches show that the codoping of non-luminous ions into RE 3+ ions doped upconverting materials is a promising way to increase the intensity of upconversion emission.…”
Section: Introductionmentioning
confidence: 98%